A Rare Case of Amyloidosis of the Eyelid and Conjunctiva - Zaria Ali; Bertie Fernando (Case Reports in Ophthalmological Medicine)
Amyloidosis of the eyelid is uncommon and is typically associated with systemic associations. In contrast, amyloidosis of the conjunctiva is often localised with no other associations. We present a rare case of a 92-year-old gentleman with both cutaneous lid lesions and conjunctival amyloid with no systemic involvement. Biopsy demonstrated the hallmarks of amyloid and treatment has remained conservative. He remains at the department to be monitored for secondary glaucoma.